Early precursor-derived pituitary gland tissue-resident macrophages play a pivotal role in modulating hormonal balance - Henna Lehtonen; Heli Jokela; Julian Hofmann; Lauriina Tola; Arfa Mehmood; Florent Ginhoux; Burkhard Becher; Melanie Greter; Gennady G. Yegutkin; Marko Salmi; Heidi Gerke; Pia Rantakari (Cell Reports)
Summary: The pituitary gland is the central endocrine regulatory organ producing and releasing hormones that coordinate major body functions. The physical location of the pituitary gland at the base of the brain, though outside the protective blood-brain barrier, leads to an unexplored special immune environment. Using single-cell transcriptomics, fate mapping, and imaging, we characterize pituitary-resident macrophages (pitMØs), revealing their heterogeneity and spatial specialization. Microglia-like macrophages (ml-MACs) are enriched in the posterior pituitary, while other pitMØs in the anterior pituitary exhibit close interactions with hormone-secreting cells. Importantly, all pitMØs originate from early yolk sac progenitors and maintain themselves through self-renewal, independent of bone marrow-derived monocytes. Macrophage depletion experiments unveil the role of macrophages in regulating intrapituitary hormonal balance through extracellular ATP-mediated intercellular signaling. Altogether, these findings provide information on pituitary gland macrophages and advance our understanding of immune-endocrine system crosstalk.